1997
DOI: 10.1007/bf02267725
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of compression of different capacitance beds in the amelioration of orthostatic hypotension

Abstract: Orthostatic hypotension (OH) is the most disabling and serious manifestation of adrenergic failure, occurring in the autonomic neuropathies, pure autonomic failure (PAF) and multiple system atrophy (MSA). No specific treatment is currently available for most etiologies of OH. A reduction in venous capacity, secondary to some physical counter maneuvers (e.g., squatting or leg crossing), or the use of compressive garments, can ameliorate OH. However, there is little information on the differential efficacy, or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(96 citation statements)
references
References 13 publications
2
92
1
1
Order By: Relevance
“…A reduction in venous capacity, secondary to some physical counter manoeuvres (e.g., squatting or leg crossing), or the use of compressive garments, can ameliorate orthostatic hypotension. Compression of all compartments is the most efficacious, followed by abdominal compression, whereas leg compression alone was less effective, presumably reflecting the large capacity of the abdomen relative to the legs (Denq et al, 1997). Another study confirms that in patients with neurogenic orthostatic hypotension, abdominal compression (somewhat mimicking that occurring during squatting) increases standing BP to a varying degree by increasing stroke volume (Smit et al, 2004).…”
Section: ) Patients With Autonomic Failure and Orthostatic Hypotensionmentioning
confidence: 76%
“…A reduction in venous capacity, secondary to some physical counter manoeuvres (e.g., squatting or leg crossing), or the use of compressive garments, can ameliorate orthostatic hypotension. Compression of all compartments is the most efficacious, followed by abdominal compression, whereas leg compression alone was less effective, presumably reflecting the large capacity of the abdomen relative to the legs (Denq et al, 1997). Another study confirms that in patients with neurogenic orthostatic hypotension, abdominal compression (somewhat mimicking that occurring during squatting) increases standing BP to a varying degree by increasing stroke volume (Smit et al, 2004).…”
Section: ) Patients With Autonomic Failure and Orthostatic Hypotensionmentioning
confidence: 76%
“…Furthermore, Denq et al (1997) found that compression (at +40 mmHg) of the lower abdomen, thighs and calves attenuated tilt-induced reductions in BP. Such compression reduces venous pooling by reducing the overall venous cross-sectional area of the lower limb (thereby increasing the linear velocity of venous outflow), reducing venous distension, and by enhancing the emptying of valvular cusps (Agu et al 1999).…”
mentioning
confidence: 92%
“…15,30,41,43 One of the non-pharmacological alternatives commonly used in individuals with orthostatic hypotension is the application of external counterpressure in order to decrease capacitance of the vasculature beds in legs and abdominal cavity -the major areas of blood pool during standing. 40,41,[44][45][46] Previously, numerous studies evaluated effects of chest and abdominal binders on cardiovascular parameters owing to increased intrathoracic pressure. 47,48 The authors reported that changes in intrathoracic pressure were associated with reciprocal changes in both intrathoracic vascular pressures and blood volume.…”
Section: Steelementioning
confidence: 99%
“…Denq et al 45 reported that compression of the abdomen is by far the most effective site to improve standing arterial pressure in patients with orthostatic hypotension. More recently, Smit et al 41 in a cohort of 23 individuals with orthostatic hypotension of varying etiology also demonstrated that abdominal compression significantly improves upright blood pressure by an increase in stroke volume.…”
Section: Steelementioning
confidence: 99%